Wild [compact disc, unabridged] : from lost to found on the Pacific Crest Trail - Strayed, Cheryl, 1968- (Random House, 2012)
A powerful, blazingly honest, inspiring memoir: the story of a 1,100 mile solo hike that broke down a young woman reeling from catastrophe--and built her back up again.